2008
DOI: 10.1002/rra.1152
|View full text |Cite
|
Sign up to set email alerts
|

A multi‐tracers analysis of sources and transfers of particulate organic matter in a tropical reservoir (Petit Saut, French Guiana)

Abstract: We measured the organic carbon (OC) content, the isotopic composition, the C/N ratios and the photosynthetic pigment composition of suspended matter, sediments, sediments traps and epiphytic and epilithic biofilms at the tropical Sinnamary River system (French Guiana). Our sampling included the mid-stream reservoir lake (Petit Saut) and the estuary on the Atlantic coast. These tracers were complementary and allowed identifying different sources of particulate organic matter (POM) in the system. We found a d 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 42 publications
3
11
0
Order By: Relevance
“…Such observations have previously been reported from the Black Sea and other anoxic zones (Sinninghe Damste et al, 1993;Chen et al, 2001;Squier et al, 2002). A recent study of pigment composition in Petit Saut, a tropical reservoir in French Guiana, showed the dominance of Chlorophyceae (Chl a, Chl b and lutein) in the oxic epilimnion, and anoxygenic photo-autotrophic bacteria below the oxycline as revealed by BChl c and BChl d (Junet et al, 2009). An example of how the community structure of phytoplankton is dependent on nutrient availability is provided by the results of Zhu et al (2010) from Taihu Lake (China) where Chlorophyta were found to be predominant at high concentrations of nitrogen and phosphorus, whereas cyanobacteria dominated in waters having low concentrations of these nutrients.…”
Section: Comparison Of Phytoplankton Assemblages During Summer Stratisupporting
confidence: 74%
“…Such observations have previously been reported from the Black Sea and other anoxic zones (Sinninghe Damste et al, 1993;Chen et al, 2001;Squier et al, 2002). A recent study of pigment composition in Petit Saut, a tropical reservoir in French Guiana, showed the dominance of Chlorophyceae (Chl a, Chl b and lutein) in the oxic epilimnion, and anoxygenic photo-autotrophic bacteria below the oxycline as revealed by BChl c and BChl d (Junet et al, 2009). An example of how the community structure of phytoplankton is dependent on nutrient availability is provided by the results of Zhu et al (2010) from Taihu Lake (China) where Chlorophyta were found to be predominant at high concentrations of nitrogen and phosphorus, whereas cyanobacteria dominated in waters having low concentrations of these nutrients.…”
Section: Comparison Of Phytoplankton Assemblages During Summer Stratisupporting
confidence: 74%
“…The x-and y-axes representing OC mineralization rates are on a log scale. perimeter ratios; and the quality of the OC available for mineralization, which is potentially more processed due to partial mineralization prior to entry into the reservoir (De Junet et al 2009). However, it is important to highlight that reservoirs had generally lower temperature ranges than other systems (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The usually high nutrient availability of fluvial inflow and the gradual decrease in turbulence towards the dam lead to rivers-dam gradients of, for example, sediment accumulation rates and sedimentary OC sources in reservoirs (De Junet et al, 2009). The combined effect of an increase in the relative contribution of more labile autochthonous-derived OC (further discussed below) and a decreasing sediment accumulation rate result in a decrease in OCBE towards the dam (p = 0.01; r = 0.69).…”
Section: Rivers-dam Gradientsmentioning
confidence: 99%
“…While spatial variation in CO 2 emissions from reservoirs' surface to the atmosphere have been described (Roland et al, 2010), the effect of heterogeneity on the sediment-carbon flows is unknown, even though reservoir heterogeneity is clearly reflected in sediment characteristics (De Junet et al, 2009). The main purpose of this study was to determine the OCBE in a subtropical hydroelectric reservoir, and to evaluate the importance of variable factors driving it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation